2014
DOI: 10.4103/1477-3163.146506
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer review

Abstract: Gastric cancer is an aggressive disease that continues to have a daunting impact on global health. Despite an overall decline in incidence over the last several decades, gastric cancer remains the fourth most common type of cancer and is the second leading cause of cancer-related death worldwide. This review aims to discuss the global distribution of the disease and the trend of decreasing incidence of disease, delineate the different pathologic subtypes and their immunohistochemical (IHC) staining patterns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
151
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 60 publications
(86 reference statements)
2
151
0
3
Order By: Relevance
“…High incidence of metastasis remains the main cause of mortality in patients with gastric cancer (19). Cell invasion is an important feature associated with tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…High incidence of metastasis remains the main cause of mortality in patients with gastric cancer (19). Cell invasion is an important feature associated with tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cancer prevention studies have demonstrated that the most effective way to reduce GC-associated mortality is through early diagnosis and appropriate treatment (2)(3)(4). However, the diagnosis rate of early GC remains extremely low (<10%) (5).…”
Section: Introductionmentioning
confidence: 99%
“…The major histological type of GCs are adenocarcinomas, which are subdivided into intestinal type, diffuse type and mixed/unclassifiable type by Lauren classification (3). Previous studies have demonstrated that intestinal and diffuse types of GC evolve via distinct genetic pathways (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%